Innovative business models for E-learning entrepreneurs - Sambhanthan, A.; Potdar, Vidyasagar (2017)
Copyright Â© 2017, IGI Global. This paper reports a state of the art literature survey undertaken on innovative e-learning business models. A review of existing business models of e-learning providers is undertaken. Three business model classification approaches for e-learning businesses are adapted for the evaluation. The e-learning business models are classified into three main categories namely managerial classification, service oriented classification and economic classification. We have then classified the literature in this line and present a priori framework developed for evaluating the e-Learning business enterprises. The research concludes with a summary of classification approaches available in the existing e-learning business domain.